Ferroelectric nanofibers with an embedded optically nonlinear benzothiazole derivative - Baptista, Rosa M. F.
We report measurements of the molecular first hyperpolarizability, thermal stability, photophysical, piezoelectric, and ferroelectric properties of a benzothiazole derivative bearing an arylthiophene pi-conjugated bridge both in solution and when embedded into a poly (l-lactic acid) matrix in the form of electrospun fibers with an average diameter of roughly 500 nm. The embedded nanocrystalline phenylthienyl-benzothiazole with crystal sizes of about 1.4 nm resulted in a good piezoelectric response from these functionalized electrospun fibers, indicative of a polar crystalline structure.